2022
DOI: 10.33899/magrj.2022.135131.1192
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Some Aphid Species (Homoptera; Aphididae) Based on RFLP-PCR Technique

Abstract: This work includes, identification eight species of Aphids (Homoptera: Aphididae) which collected from the leaves of different plants in many localities of Erbil governorate Kurdistan region-Iraq from the period May till July 2022, these are: Chaitophorus salijaponicus, Aphis fabae, Macrosiphum rosae, Capitophorus carduinus, Myzus persicae, Aphis ruborum, Aphis punca, and Aphis gossypii. The mitochondrial cytochrome C Oxidase subunit I (COI) gene used for identification these species. DNA was isolated, and a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2025
2025
2025
2025

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Proper identification is the initial stage in pest management, and DNA-based techniques are the most effective approach for identifying insect species from every position. Therefore, the results demonstrated that COI-DNA determination was highly effective for almost every insect species [33]. Nowadays, the MT-COI gene has the advantage of avoiding confusion in the presence of polymorphism as well as throughout the different life stages and sexual forms of the species being examined.…”
Section: Discussionmentioning
confidence: 96%
“…Proper identification is the initial stage in pest management, and DNA-based techniques are the most effective approach for identifying insect species from every position. Therefore, the results demonstrated that COI-DNA determination was highly effective for almost every insect species [33]. Nowadays, the MT-COI gene has the advantage of avoiding confusion in the presence of polymorphism as well as throughout the different life stages and sexual forms of the species being examined.…”
Section: Discussionmentioning
confidence: 96%